ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN SOSIOLOGI OLEH GURU KELAS XI IIS SMA N 2 MEMPAWAH HULU - Dayana, Chinthis Ayu; Buwono, Sri; Alhidayah, Riama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to determine the media and the use of sociological learning media in the class XI IIS SMA N 2 Mempawah Hulu. This study used is qualitative approach with descriptive methods. Data collection techniques used are observation, interviews, and documentation studies; The analysis in this study was presented in a qualitative descriptive manner user informants as much as five people consisting of a teacher of sociology learning and student of class XI IIS. Learning media is a form of physical in a planned manner to convey information and build interaction. The media used are a visual display, visual print, and visual images. Stage in the use of learning media namely the preparation and planning, the implementation, and the flow-up stage. In the learning process of material learning delivered by the teacher are encoding and student decoding. In the use of learning media, there are obstacles (barriers or noises). The teacher of sociology learning looks at the results of the media by providing evaluations, measurement, and values to see how effective and learning outcomes are given. Keywords: Media, Media Use, Sociology Learning, SMA N 2 Mempawah Hulu